Genetic parameters and selection indices for Hampshire lambs and ewes under an intensive breeding in a flock of the central coast of Peru - Carrera, Iván (2015)
The study aimed to characterize for genetic improvement purposes an ovine Hampshire flock located in the central coast of Peru. Genetic and phenotypic parameters were estimated for Birth Litter Size (TCN), Litter Weaning Weight (PCD), 2-Month Weaning Weight (PD), 5-Month Slaughter Weight (PB), and Body Weight Gain from Weaning to 5 Months Old (GPD5); and selection indices for lambs (I1 and I2) and ewes (I3) were developed using data collected between 2002 and 2004. Components of the variance and covariance were estimated using the Restricted Maximum Likelihood method (REML), under a mixed model that included sex, type of birth, season and year of birth as fixed effects, and sire as random effect. Phenotypic mean values estimated for body weight traits in lambs and productive and reproductive traits in ewes were similar to the breed standard reared under medium technology systems. The estimated genetic parameters corresponded to those reported in the literature except the TCN (0.26 ± 0.28) and PB (0.36 ± 0.21) heritabilities which were above and below the values commonly reported elsewhere, respectively. All genetic and phenotypic correlations among body weights showed medium to high positive values. Lamb selection indices had the expressions: I1 = 4.782*PB + 2.864*GPD5 e I2 = 8.263*PD + 3.182*PB + 4.164*GPD5, with correlation coefficients of 0.415 and 0.527, respectively; and for ewes I3 = + [n*0.0153/ 1 + (n-1)*0.0153]* ( - ), which could be applied for selection purposes but with relative efficiency